FROM MOUNT MUSA TO SINJAR MOUNT. COMPARATIVE ANALYSIS OF SELF-DEFENSE FIGHTS - Marukyan, Armen (Armenian Folia Anglistika, 2024)
The study of self-defense battles of victim groups during genocides is no less important than the study of the crimes themselves. The purpose of this article is to study the self-defense battles of Armenians during the Armenian Genocide in the Ottoman Empire and the Yazidi Genocide carried out by ISIS in the Iraqi province of Sinjar (Shangal). In particular, the article provides a comparative analysis between the self-defense battles of Mount Musa and Mount Sinjar (Shangal). The study combines historical-comparative and analytical methods to achieve the stated goals and objectives. The article has used both primary and secondary sources, as well as interdisciplinary research by specialists. As a result of the comparative analysis conducted in the article, both common features and differences were revealed between the self-defense battles of Mount Musa and Mount Sinjar during the Armenian Genocide and the Yazidi Genocide. Despite the almost century-long period separating these two cases, there are certain similarities and significant differences between the self-defense of the Armenians and the Yazidis. To emphasize the rejection of genocides in the world, I dedicate this article to the 90th anniversary of The Forty Days of Musa Dagh.